Two philanthropic institutions for one purpose in different ways: utilisation of religious philanthropy in terrorism financing in Indonesia - Novi Dwi Nugroho; Daniel Rabitha; Retno Kartini Savitaningrum Imansah; Ahsanul Khalikin (Cogent Social Sciences)
Jemaah Islamiyah is a banned terrorist group in Indonesia that has been known to raise funds through faith-based philanthropic institutions. Baitul Maal Abdurrahman Bin Auf (BM ABA) and Syam Organizer (SO) are among these institutions that have been identified as the ones that serve as a 'funding machine' for the group. A case study explored the mechanisms BM ABA and SO used to collect religious philanthropy funds to support Jemaah Islamiyah. The study found that the use of faith-based philanthropic institutions for financing terrorism in Indonesia may involve different methods but can be aimed at the same terrorist group. BM ABA tends to rely on charity boxes and donation cans, while SO primarily uses tabligh akbar (the recitation invited many people) as a means of gaining public sympathy. This research can help the Indonesian government determine charitable practices that can avoid abuse by terrorist groups. Preventing terrorism financing during the fundraising process is the primary step before continuing to the transfer and use of terrorism funds. The Indonesian government needs a mechanism to supervise faith-based philanthropic institutions and cohesively coordinate with related institutions. This monitoring mechanism can refer to the cases studied in this research study.